Difficulties of diagnostics of acute myocardial infarction in elderly and senile patients and their influence on management in the acute period of disease - O. V. Tukish; A. A. Garganeeva (Российский кардиологический журнал, 2019)
Aim. To study the features of disease progress and approaches to the diagnostics of acute myocardial infarction (MI) among elderly and senile patients and their influence on the management in the acute period of disease.Materials and methods. The study was performed using the WHO program “Register of acute myocardial infarction” (Tomsk). The study included 410 patients (60 years and older), who had acute MI. The study group is represented by a comparable number of men (n=212) and women (n=198). The mean age of patients was 71 (66; 77) years (women are 5 years older than men (p<0,001)). Statistical processing was performed using the program Statistica V10.0.Results. Most of the patients had history comorbid pathology. In one in five patients (17,8%), the disease had an atypical manifestations, which in 41% of cases was represented by the asymptomatic form. Atypical manifestation of MI lengthened the prehospital phase of medical care due to a longer time before the first medical contact (p=0,005), as well as a late help-seeking (120 [49; 311,5] minutes). In 28% of patients, the level of creatine kinase-MB remained normal, and the indicator of troponin I exceeded the maximum values only in half of the cases. One fifth of the patients underwent acute MI treatment in non-core hospitals, which resulted in a low frequency of intervention (38%) and increasing by 2 times the chance of death within 5 years. The level of hospital mortality from acute MI in elderly patients in noncore hospitals was 3 times higher than in specialized departments (p<0,001).Conclusion. Difficulties in diagnostics of MI in patients of older age groups is caused by the prevalence of comorbid pathology, an atypical manifestations of the disease and low information content of biochemical markers of myocardial necrosis. It leads to an increase in time delays at the prehospital phase and frequent hospitalization of patients in non-core hospitals, making it impossible for them to receive timely, preferred therapy.